THE LEGAL NATURE OF ATTORNEY DELEGATION - Pouladi, Ali; Gholami, Jahanbakhsh; Ghanbarpour, Behnam (International Journal of Psychosocial Rehabilitation, 2020)
Appointing deputation means delegation of power to a third party attorney. In the theory of delegation to a third party, defining the attorney’s position and its consequences can be of great importance. It is very important to define if the third party’s authority is the same or partial as that of the first attorney and can lead to different consequences. After delegating to another one, each attorney’s authority can also be investigated. Based on the foregoing, this research has been conducted to define the difference between delegation and appointing in Iranian jurisdiction. Based on the results of this study , despite appointing in which the attorney is still in authority, in delegation the first attorney will not be in authority after defining a third party. It seems that due to its function, this topic is of great importance in the attorney contract. Attorney contract is a kind of optional contract in which mutual confidence, especially the customer’s confidence in his attorney matters.